THE INFLUENCE ANALYSIS OF HALAL CERTIFICATE, HALAL AWARNESS, BRAND IMAGE AND RELIGIOSITY ON DECISIONS TO PURCHASE HALAL PRODUCT (STUDY ON STUDENTS PONDOK PESANTREN SALAFIYAH ABU ZAIRI BONDOWOSO) - Raharto, Eko; Supriyanto, Supriyanto; Dienillah, Izzah (Lan Tabur: JURNAL EKONOMI SYARIAH, 2024)
The development of halal products in Indonesia and the world is increasing, this has also increased students' interest in purchasing halal cosmetic products. This research aims to find out the influence of halal certificate, halal awareness, brand image, and religiosity on students' purchasing decisions about halal cosmetic products. The research method used is a quantitative approach with a sampling technique or purposive sampling of respondents, namely students who use halal cosmetics, data collection techniques using questionnaires distributed to 57 students of the Pondok Pesantren Salafiyah Abu Zairi Bondowoso. To analyze the research data, SPSS version 25.0 software was used. The research results show that halal certificate and brand imag, have a significant effect, while halal awareness and religiosity does not have a significant effect on the decision to purchase halal products.